Evolutionary Origins of the Endowment Effect: Evidence from Hunter-Gatherers - Apicella, Coren L.; Azevedo, Eduardo M.; Christakis, Nicholas A.; Fowler, James H. (American Economic Review, 2014)
The endowment effect, the tendency to value possessions more than non-possessions, is a well-known departure from rational choice and has been replicated in numerous settings. We investigate the universality of the endowment effect, its evolutionary significance, and its dependence on environmental factors. We experimentally test for the endowment effect in an isolated and evolutionarily relevant population of hunter-gatherers, the Hadza Bushmen of Northern Tanzania. We find that Hadza living in isolated regions do not display the endowment effect, while Hadza living in a geographic region with increased exposure to modern society and markets do display the endowment effect. (JEL C93, D12, O15)